Special education teachers and their teaching identity: A systematic review of research trends (Revista INTEREDU11, 2021)
This article presents a review of over than 50 studies related to the teaching identity of special education teachers in inclusive-education contexts. The search was carried out on free-access and on paid scientific databases, through deep readings of master and doctorate theses, and national and international studies. The systematization of information was focused on the research and analysis of titles and themes, purposes, methodologies, results and conclusions; which were taken from the basis of the doxographic matrix model (Murcia and Ospina, 2012). The results focus on internships, teacher training, current regulations and the requirements of inclusive education for teachers. In conclusion, while research has come close to establishing how teaching identity in general is built and evolved, only few studies which address how the teaching identity of special-education teachers is configured and reconfigured were found.